If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-2(x+3)=9
We move all terms to the left:
4x-2(x+3)-(9)=0
We multiply parentheses
4x-2x-6-9=0
We add all the numbers together, and all the variables
2x-15=0
We move all terms containing x to the left, all other terms to the right
2x=15
x=15/2
x=7+1/2
| -5y+39=-7(y-7) | | 4x-2(x+3)=5 | | -22=-5x-2 | | 2.6x=1.5x+5.1 | | X+-8+x=55 | | 18+6x-12(2)=2x+10 | | 9x+7x+34=180 | | F(2)=1.8x=32 | | -9/10a-2=5 | | 2.5(-10+4x)=25 | | x3-3=40 | | F(1)=1.8x=32 | | -2(4-7x)=24x-8-10 | | 0.4(x+8)=16 | | 1/3k+800=1/2k+120 | | 5(y+1/3)=45 | | F(0)=1.8x=32 | | -(22-7t/41)=-1 | | u-4=22 | | 92=(3b+5) | | -0.8-1=3.2x+5 | | 105+30=x | | w÷ 5 = 34 | | 60w=90 | | -32-6x=53 | | -2y+21=-33 | | 9x+7x=34=180 | | -4x+9/7=-1 | | 0=–x3–1 | | 6=-z/8 | | 4/5=23x | | w÷5=3/4 |